Duodenal neuroendocrine cells and neuromedin U in subjects with obesity: Relationship with type 2 diabetes and glucose homeostasis - Bur, Hassan; Hukkanen, Janne; Savolainen, Markku J.; Koivukangas, Vesa; Karttunen, Tuomo J. (Physiological reports, 2025)
Duodenal endocrine cells contribute to the incretin response, yet their changes in obesity and type 2 diabetes (T2D) remain controversial. We quantified expression of chromogranin A, glucagon‐like peptide‐1 (GLP‐1), serotonin, and neuromedin U (NmU) in duodenal biopsies from 34 participants with obesity (19 with T2D, 15 without) and six healthy controls. Compared to controls, the patients with obesity showed significantly higher proportions of chromogranin A ( p = 0.007), GLP‐1 ( p = 0.006), and serotonin ( p = 0.013) expressing cells, irrespective of T2D status. GLP‐1 expression correlated with HbA1C ( r = 0.454, p = 0.005) and meal test glucose ( r = 0.455, p = 0.0018) but not with insulin. Chromogranin A expression correlated with both GLP‐1 ( r = 0.486, p = 0.003) and serotonin ( r = 0.475, p = 0.003), as well as BMI ( r = 0.429, p = 0.007). NmU was detected in the lamina propria but did not differ among groups. For NmU, an association with insulin (incremental AUC, r = 0.363, p = 0.045) was observed. In conclusion, obesity was associated with hyperplasia of duodenal GLP‐1, serotonin, and chromogranin A cells. The link between GLP‐1 expression, HbA1C, and meal test glucose indicates that, despite increased numbers of GLP‐1–producing cells, individuals with obesity may still experience insufficient incretin action. No evidence supported a role for NmU as a human decretin in these patients.